Instructional Intelligence in Improving Learning Environment: Where Does the Practicing Teacher as an Auto-Ethnogrphic Researcher Stand? - Sana Ayaz; Dr. Abdul Ghaffar; Dr. Samreen Mehmood, (Dialogue Social Science Review (DSSR), 2025)
Pre-service teachers, instructors and trainers learn about cutting edge, student-centered teaching practices through their undergraduate studies in order to improve their professional teaching practice after entering the field of education. But I discovered that many of them were not putting their new knowledge into practice. They appear to only use the traditional (teacher-centered) method of instruction and learning in their classes. In order to research this topic, I created a arts-based critical auto/ethnographic technique through which I was able to deeply engage in critical reflection on my prior teaching experiences and develop a critical understanding of them. This approach draws on three main paradigms Interpretivism (the world as it is), Criticalism (how the world should be?), Postmodernism (how the world may be?). Three of my former coworkers who are currently teachers and trainers participated with me to conduct focused, structured interviews. To inform their thinking of innovative teaching practices, they must adopt a critical constructivist epistemology rather than a prescriptive method of instruction. This epistemology opens up a range of options for considering important factors, including the teaching framework, the philosophy of instruction and acquisition, and individual epistemologies, which have an effect on their professional career.